Evaluation of Clinical Efficiency of Cardioprotective Therapy in Patients with Acute Myocardial Infarction - I. D. Astrakhantseva; A. S. Vorobyov; K. Yu. Nikolayev; I. A. Urvantseva (Неотложная медицинская помощь)
Aim. To evaluate the efficiency of cardioprotective therapy using intravenous metoprolol in combination with a high dose of atorvastatin in the prevention of myocardial remodeling (MR) and heart failure (HF) in patients with acute ST-segment elevation myocardial infarction (STEMI).Material AND methods. A prospective study included 100 STEMI patients who underwent primary percutaneous intervention (PCI). Depending on the regimens of drug cardioprotection, three groups of patients were formed: the first (2014–2015) — 34 patients who received 80 mg atorvastatin as a part of the basic therapy on the first day of STEMI, then 20–40 mg/day for 30 days. The second group (2017–2018) — 34 patients who received atorvastatin 80 mg/day for a month from the onset of STEMI. The third group (2018–2019) — 32 patients who received intravenous metoprolol tartrate (5–15 mg) and atorvastatin 80 mg/day before PCI for a month from the onset of STEMI. On days 1 and 2 of STEMI and one month later, patients were assessed for serum levels of cardiac biomarkers; on the 1st, 7th days and one month later, echocardiographic studies (EchoCG) were performed. At the end of the observation, clinical and imaging outcomes (MR and HF) were assessed, which were compared with the dynamics of biomarkers between the groups of patients.Results. The combined use of atorvastatin 80 mg/day for a month from the onset of STEMI and a single intravenous injection of metoprolol tartrate (5–15 mg) in the acute phase of STEMI before PCI showed the most significant effects in the prevention of the development of structural and functional myocardial disorders and clinically severe heart failure, and also caused the minimal serum activity of cardiomarkers in the third group of patients in comparison with the first and second groups of patients without this drug combination. Also, correlations between biomarkers and echocardiography indicators were established in the third group of patients who received cardioprotective therapy.Conclusion. The combined use of high-dose atorvastatin for a month with a single intravenous injection of metoprolol tartrate in acute STEMI before PCI prevents the formation of MR and clinically significant HF in the post-infarction period. Comprehensive dynamic assessment of cardiac biomarkers and echocardiography parameters within a month after post-STEMI is a highly informative tools for monitoring the efficiency of cardioprotective therapy.